Short Term Outcome of Adjunct Foam Sclerotherapy for Varicose Veins in Patients Subjected to RFA at Dhulikhel Hospital, Nepal - R. M. Karmacharya; B. Shrestha; A. Singh; N. Chandi; N. Bhandari (International Journal of Vascular Medicine)
Background. Varicose veins are dilated, tortuous, superficial veins usually seen on lower limbs. Various surgical modalities are available for varicose veins including open surgery (Trendelenburg operation), Endovenous Laser Ablation (EVLA), Radiofrequency Ablation (RFA) and Sclerotherapy. The aim of this study is to look for the outcome of adjunct sclerotherapy for varicose veins done as an adjunct with Radio Frequency Ablation. Objective. To know the possible outcome regarding benefits and complications of adjunct sclerotherapy with Radio Frequency Ablation. Methodology. We combined Radio Frequency Ablation of varicose veins with necessary phlebectomy and perforator ligation and performed adjunct sclerotherapy for residual significant varicosities with polidocanol (2%) mixed with 2 ml NS and 2 cc of air (Tessari method) to patients undergoing varicose vein surgery in between 2016 and 2017. Records on complications were enquired immediately following surgery and on 1st follow up done within 3–5 days of the procedure. Results. Among 256 limbs subjected to varicose veins surgery 51 limbs were given adjunct sclerotherapy. Among them, five limbs had perivenous spillage with some localized swelling while there was allergic reaction in one patient as immediate postprocedural complication. Nine limbs had painful thrombosed veins during early follow-up. Conclusions. Adjunct sclerotherapy showed complication rate of roughly one tenth and one fifth of the treated cases in immediate and early postoperative follow-up.